Tips for Distinguishing Nominal and Ordinal Scale Data - Suparji Suparji; Heru Santoso Wahito Nugroho; Wiwin Martiningsih (Aloha International Journal of Multidisciplinary Advancement (AIJMU), 2021)
In community empowerment research, categorical variables both in the form of nominal and ordinal scales are often involved. The purpose of these tips is to provide information on how to distinguish nominal and ordinal variables, so that data interpretation errors do not occur. In principle, to distinguish nominal and ordinal variables, the first step is to ensure that there is a dichotomy which means variables at nominal scale; if there are more than two categories, a second step is taken, namely to ensure that there are differences in degree between categories which means the variables are ordinal scale. Keywords: categorical variable, nominal scale; ordinal scale; distinguishing